Evaluation of the 2‐(1‐Hexyloxyethyl)‐2‐devinyl pyropheophorbide (HPPH) mediated photodynamic therapy by macroscopic singlet oxygen modeling [J. Biophotonics 9, No. 11–12, 1344–1354 (2016)]. Issue 3 (6th February 2017) - Penjweini, Rozhin; Kim, Michele M.; Liu, Baochang; Zhu, Timothy C.
Abstract : In the article by R. Penjweini, M. M. Kim et al. (doi:10.1002/jbio.201600121 ), published in J. Biophotonics 9, 1344–1354 (2016), the constants C 01, C 02, b 1, and b 2 determined from fitting the fluorescence single value decomposition (SVD) for phantoms with different optical properties and the corresponding Figure 2(a) are not correct. This erratum is published to correct the Section 2.3 and Figure 2(a).